Leptin as well as Free Leptin Receptor Is Associated with Polycystic Ovary Syndrome in Young Women - Nasser M. Rizk; Elham Sharif (International Journal of Endocrinology)
Background and Aim. Leptin has two forms in the circulation: free and bound forms. The soluble leptin receptor (sOB-R) circulates in the blood and can bind to leptin. The aim of this study is to assess the concentrations of the leptin and the sOB-R in PCOS and its relation to adiposity, insulin resistance, and androgens. Methods. A cross-sectional study included 78 female students aged 17–25 years. Fasting serum leptin and sOB-R concentrations were measured. The anthropometric variables and the hormonal profile such as insulin, female and male sex hormones, and prolactin were assessed. Results. In PCOS, leptin level (ng/ml) and free leptin index (FLI) increased significantly while sOB-R (ng/ml) significantly decreased compared to control subjects. In age-matched subjects, obese PCOS had increased leptin level in ng/ml (median level with interquartile levels) of 45.67 (41.98–48.04) and decreased sOB-R in ng/ml 11.47 (7.59–16.44) compared to lean PCOS 16.97 (10.60–45.55) for leptin and 16.62 (11.61–17.96) for sOB-R with p values 0.013 and 0.042, respectively. However, body mass index (BMI) is significantly correlated with leptin and s-OBR, while no significant correlations with parameters of insulin resistance were detected. Conclusion. PCOS is associated with hyperleptinemia and increased free leptin index. Decreased sOB-R could be a compensatory mechanism for the defective action of leptin.